METODE PEMBAYARAN BELANJA DENGAN E-COMMERCE - Lita Sari Marita (Universitas Bina Sarana Informatika, 2012)
To buy something nowdays it’s not have to go out from our home and spending time at the market, however the fact we don’t find what we looking for. Shoping with a conventional way it’s being leaving from people, nowdays people more like to spend their time to shop with shoping in the internet. It causes of the pratcical and not spending much time on way. But people still doing shoping with a convensional way otherwise to have another benefits is fun in the mal. Shoping in the internet need tools it’s a computer n an internet, shop that is serving people with this facilities called a commerce, so many market serving with this facilites, and ofcourse the have many bemefits of it. Keywords : a commerce, shoping